The Evolving Definition of Advanced Prostate Cancer - Moul, Judd W (MedReviews, LLC, 2004)
Each year more patients present with prostate cancer at increasingly younger ages and with earlier stage disease, resulting in the potential for longer survival time, longer-term hormonal therapy, and a heightened risk of developing biochemical recurrence after treatment. It seems clear that clinicians need to broaden the definition of “advanced” prostate cancer to include recent knowledge that will influence the form and timing of treatment as well as the monitoring of disease progression. A more contemporary definition should include patients with lower-grade disease and with an increased risk of progression and/or death from prostate cancer along with those with widely disseminated metastatic disease. Treatment alternatives for these patients should be evaluated based on a risk stratification equation toward a goal of the greatest efficacy and the least patient harm over time given that increasing numbers of these patients are entering treatment long before they develop widespread osteoblastic metastases.